Link-preserving channel assignment game for wireless mesh networks. (14th May 2019) - Yen, Li-Hsing; Ye, Bo-Rong
To deliver user traffic in a wireless mesh network (WMN), mesh stations equipped with multiple interfaces communicate with one another utilising multiple orthogonal channels. Channel assignment is to assign one channel to each interface to minimise co-channel interference among wireless links while preserving link connectivity. The interference and connectivity objectives are generally conflicting. This paper first analyses the probability of link connectivity when channels are randomly assigned to interfaces. We then propose a game-theoretic approach that jointly considers the two objectives with a unified payoff function. We prove that the proposed approach is an exact potential game, which guarantees stability in a finite time. We also prove the link-preserving property of the approach. Simulation results show that the proposed approach generally outperforms counterparts in terms of network interference when a moderate number of channels are available. For fairness of link interference, both the proposed approach and its variant outperform the counterparts.